The Value of Circulating Tumor Cells in the Prognosis and Treatment of Pancreatic Cancer - Luo, Kai; Wang, Xiangkun; Zhang, Xudong; Liu, Zhongyuan; Huang, Shuai; Li, Renfeng (Frontiers in Oncology, 2022)
In the past few decades, tumor diagnosis and treatment theory have developed in a variety of directions. The number of people dying from pancreatic cancer increases while the mortality rate of other common tumors decreases. Traditional imaging methods show the boundaries of pancreatic tumor, but they are not sufficient to judge early micrometastasis. Although carcinoembryonic antigen (CEA) and carbohydrate antigen19-9 (CA19-9) have the obvious advantages of simplicity and minimal invasiveness, these biomarkers obviously lack sensitivity and specificity. Circulating tumor cells (CTCs) have attracted attention as a non-invasive, dynamic, and real-time liquid biopsy technique for analyzing tumor characteristics. With the continuous development of new CTCs enrichment technologies, substantial progress has been made in the basic research of CTCs clinical application prospects. In many metastatic cancers, CTCs have been studied as an independent prognostic factor. This article reviews the research progress of CTCs in the treatment and prognosis of pancreatic cancer.